Evaluating the efficiency of mandibular molar protraction using Herbst appliances versus temporary anchorage devices: a retrospective case-controlled study - Ishita Z. Taneja; Guihua Zhai; Neal D. Kravitz; Bill Dischinger; Mark Johnston; Chung-How Kau; Ejvis Lamani (SpringerOpen, 2024)
Abstract Background Mandibular second premolar agenesis is a common problem in orthodontics and is often treated in conjunction with maxillary counterbalancing extractions. However, in cases without maxillary crowding or dental protrusion, space closure may pose challenges leading to compromised occlusal results or patient profile. Multiple techniques have been described to treat these patients; nevertheless, there is a paucity of data comparing effectiveness of space closure utilizing various anchorage techniques. The goal of this study is to assess the effectiveness of the Herbst device during mandibular molar protraction and compare it to the use of temporary anchorage device (TADs) in patients with mandibular second premolar agenesis. Materials and methods This retrospective study included 33 patients with mandibular premolar agenesis treated without maxillary extractions. Of these patients, 21 were treated with protraction Herbst devices and 12 with TADs. Changes in molar and incisor positions, skeletal base positions and occlusal plane angulations were assessed on pretreatment (T0) and post-treatment (T1) lateral cephalograms. Scans/photographs at T0 and T1 were used to evaluate canine relationship changes representing anchorage control. Space closure and breakage/failure rates were also compared. Data was analyzed with paired and unpaired t-tests at the significance level of 0.05. Results Within the Herbst group, changes in mandibular central incisor uprighting and mandibular molar crown angulations were statistically significant. However, no significant differences were noted between the Herbst and TAD groups. Protraction rates as well as overall treatment times were comparable (0.77 mm/month vs. 0.55 mm/month and 3.02 years vs. 2.67 years, respectively). Canine relationships were maintained or improved toward a class I in 82.85% of the Herbst sample, compared to in 66.7% of the TAD sample. Emergency visits occurred in 80.1% of the Herbst group, with cementation failures or appliance breakages as the most common reasons. Conclusion The Herbst device could be a viable modality in cases with missing mandibular premolars where maximum anterior anchorage is desired, or if patients/parents are resistant to TADs. Furthermore, they could be beneficial in skeletal class II patients with mandibular deficiency who also need molar protraction. However, the increased incidence of emergency visits must be considered when treatment is planned.